Evaluation of patient comfort and Impact of different anesthesia techniques on the temporomandibular joint arthrocentesis applications by comparing gow-gates mandibular block anesthesia with auriculotemporal nerve block - ATALI, ONUR; GÖNÜL, ONUR; GARİP, HASAN (My University, 2022)
Aim. Temporomandibular disorders (TMDs) are clinical situations that are characterized by pain, sound, and irregular movements of the temporomandibular joints. The most common method in the treatment of TMDs is arthrocentesis. This study aims to compare the effect of conventional extraoral auriculotemporal nerve block (ANB) and Gow-Gates (GG) mandibular anesthesia techniques on patient comfort in an arthrocentesis procedure. Materials and Methods. We performed this study on 40 patients who underwent TMJ arthrocentesis with ANB (n = 20) or GG (n = 20) mandibular anesthesia techniques at the Marmara University Faculty of Dentistry between 2016 and 2019. The predictor variable was the type of an anesthesia technique, and the outcome variables included were pain, maximum mouth opening (MMO), and protrusive movement (PM). They were compared at the preoperative period and 3rd and 6th month periods. Statistical analysis included means with standard deviations, a one-way ANOVA for continuous data, and the results were evaluated at the significance level of p < 0.05. Results. No statistically significant difference was observed between the VAS values, MMO, and PM averages of preoperative, 3rd and 6th months of ANB and GG (p=0.142, p=0.209, and p=0.148). Conclusion. Both anesthesia techniques have provided effective results in terms of pain and functional jaw movements in the postoperative period in arthrocentesis treatment.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Health Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Nöroloji (klinik); Yaşam Bilimleri; Neurology (clinical); Life Sciences